Developing An Innovative Web based Agricultural Management System for Sukamaju village - David, Axel; Silalahi, Panji Christoper; Herlambang, Yohanes Yogas; Kusuma, Purba Daru; Hasibuan, Faisal Candrasyah (Universitas Negeri Semarang, 2025)
Agriculture is a vital component of the economy and livelihoods in Indonesia, particularly in Sukamaju village, West Java, Indonesia. Many local farmers rely on traditional farming management methods, which hinder efficiency and productivity due to challenges such as manual data entry, inadequate tracking of crop yields, and limited avenues for product promotion. To address these issues, an Agricultural Management Web Application was developed to streamline the management of agricultural activities within the community. This user-friendly platform allows farmers to input and monitor essential data about their crops, thereby enhancing informed decision-making. Additionally, the application features a blog system for promoting agricultural products, helping farmers reach a wider audience and improve their sales prospects. Key objectives of the application include improving documentation and monitoring of agricultural processes, fostering community engagement through knowledge sharing, and providing promotional tools for farmers. By leveraging technology, this initiative aspires to establish a sustainable agricultural environment that supports the growth of the farming community in Sukamaju village. In the future, this application can be expanded to create a more comprehensive supply chain management system for farmers in a broader area. The feature also can be expanded so that the farmers can connect to the other players whether in the upstream and the downstream.